Quercetin-biapigenin nanoparticles are effective to penetrate the blood–brain barrier - Oliveira, Ana (2021)
Search for efficient therapeutic agents for central nervous system (CNS) disorders has been extensive. Nevertheless, blood-brain barrier (BBB) is an obstacle that prevents the majority of compounds to act in these diseases. It is, thus, of extreme relevance the BBB overcome, in order to deliver a drugs therapeutically active concentration to the action site, with the least losses and interaction with other organs, tissues, or cells. The present study aimed to investigate the potential protective effect of quercetin-biapigenin encapsulated into poly(Ɛ-polycaprolactone) (PCL) nanoparticles against t-BOOH-induced oxidative stress in several brain cell lines, as well as evaluate the permeability of those active molecules through an in vitro BBB model. The three cell lines under study (BV-2, hcmec/D3, and U87) presented different reactions to t-BOOH. In general, quercetin-biapigenin PCL-loaded nanoparticles were able to minimize compound toxicity they convey, regardless the cell line. Quercetin-biapigenin PCL-loaded nanoparticles (Papp of approximately 80 × 10-6 cm/s) revealed to be more permeable than free compounds (Papp of approximately 50 × 10-6 cm/s). As of our knowledge, this is the first report of quercetin-biapigenin PCL-loaded nanoparticle activity in brain cells. It is also the first determining its permeability through BBB, as an effective nanocarrier for brain delivery.